2006
DOI: 10.1002/srin.200606461
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Mineralogical Data for Influencing Properties of Coke: a Reference on Si02 Polymorphs

Abstract: 5i02 occurs in coking coals as pure quartz and also in complex aluminosilicates. At coking temperatures, pure 8i0 2 has several polymorphs (a-and J3-quartz and IHridymite) and transformations from one to another are accompanied by volume changes in the mineral matter that can lead to the formation of cavities and cracks in a coke matrix. These can weaken the coke physical strength and lead to a higher circulation of gases within the pieces. The grain size of the primary quartz crystals in a coal blend is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
(8 reference statements)
2
16
0
Order By: Relevance
“…Sukhorukov et al [56] suggested that quartz would increase the strength of coke and Patrick and Stacey [57] thought that at lower concentration quartz could increase the strength. In contrast, Patrick and Stacey [57] suggested that at higher concentration quartz would decrease the strength and Gornostayev et al [58] suggested that such a decrease in strength could be due to strain induced by changes in the mineral volume following phase transformations during carbonization. Thus the higher silica content of the coal compared to the briquettes could have been a factor in the higher strength of the coal derived products, but this remains uncertain.…”
Section: Compressive Strengthmentioning
confidence: 90%
“…Sukhorukov et al [56] suggested that quartz would increase the strength of coke and Patrick and Stacey [57] thought that at lower concentration quartz could increase the strength. In contrast, Patrick and Stacey [57] suggested that at higher concentration quartz would decrease the strength and Gornostayev et al [58] suggested that such a decrease in strength could be due to strain induced by changes in the mineral volume following phase transformations during carbonization. Thus the higher silica content of the coal compared to the briquettes could have been a factor in the higher strength of the coal derived products, but this remains uncertain.…”
Section: Compressive Strengthmentioning
confidence: 90%
“…Under high‐temperature conditions (up to 1200 °C) of coke oven, coal‐associated minerals undergo phase transformations and decomposition, including decarbonation, dehydration, dehydroxylation, and desulfurization . From sulfur‐bearing minerals, only pyrrhotite and ZnS (most likely − wurtzite) were observed in our samples of coke (Figure ).…”
Section: Resultsmentioning
confidence: 87%
“…Our calculations have shown (Figure ) that the behavior of sulfur‐bearing minerals under coke oven conditions varies substantially, observing a number of phase transformations at different temperatures as well as different amounts of sulfur released toward the end of coking process. Unlike aluminosilicates, most of the primary sulfides occurring in coals will decompose and/or transform to other phases at coking temperatures (Figure ). For that reason, not all of them can be found in metallurgical coke in their primary form.…”
Section: Resultsmentioning
confidence: 99%
“…Under coke oven conditions (temperatures up to 1200 °C), coal‐associated minerals go through phase transformations and decomposition. The later include dehydration, dehydroxylation, decarbonation, and desulfurization, so the initial composition may change substantially.…”
Section: Resultsmentioning
confidence: 99%